2015
DOI: 10.3126/ajms.v6i5.11628
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of variability of clinical presentations and brain imaging findings in children with neurocysticercosis in rural population of West Bengal

Abstract: Background: Neurocysticercosis (NCC) is a common, widely prevalent parasitic infestation of the central nervous system in children of developing countries leading to neurological morbidities. Objectives: To study the variability of initial clinical presentations and brain imaging findings in children with NCC in the rural population of West Bengal. Methods: A retrospective analysis was done in the Department of Pediatric Medicine, Burdwan Medical College, Burdwan, India from August 2011 to August 2013. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…We noticed increased prevalence (59.7%) of NCC amongst the older children (9–16 years group) compared to only 9.7% in younger (0–4 years) age group. Our results are consistent with findings from some previous studies [ 8 , 21 ]. A study carried out by Shrestha et al [ 12 ] from Nepal in school going children reported the highest prevalence of NCC (48%) in the 10–15 years age groups.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We noticed increased prevalence (59.7%) of NCC amongst the older children (9–16 years group) compared to only 9.7% in younger (0–4 years) age group. Our results are consistent with findings from some previous studies [ 8 , 21 ]. A study carried out by Shrestha et al [ 12 ] from Nepal in school going children reported the highest prevalence of NCC (48%) in the 10–15 years age groups.…”
Section: Discussionsupporting
confidence: 94%
“…A similar study carried out in Kathmandu, a hilly region of Nepal, reported that 16% of children with seizures had NCC and various studies from India have reported its prevalence to be in the range of 12–35% suggesting wide variability of NCC in different geographical regions [ 8 11 ]. The high prevalence may be due to number of factors such as high consumption of pork meat, rearing of pigs, consumption of raw vegetables, and lack of personal and environmental hygiene and sanitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similarly another study done in West Bengal, India concluded that parietal region specially on the right side was most commonly involved (61.1%). 8 Patil et al concluded that 45 % of cases had lesions in parietal lobe followed by frontal lobe involvement in 22.5 % of the cases. 12 In a study conducted in Gandaki Medical College, Nepal, about 61.2% of the lesions were found in parietal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…also found nearly 70% cases between five to nine years age group and six to 10 years age group respectively 5,7. A study in rural population of West Bengal found commonest age being a little higher than as observed by M.S Pandit et al and Yadav et al 54.9% cases were between 10 to 12 years of age 8. A study done in Rohilkhand Medical College, Bareilly on 62 subjects in the year 2013 to 2014…”
mentioning
confidence: 81%